Peran Partisipasi Publik Berbasis Digital (E-Participation) dalam Proses Perancangan Peraturan Perundang-Undangan di Indonesia: Tantangan dan Optimalisasi - Naisabur, Nanang; Mariska Salsabila, Adzanah (Cv. Kalimasada Group, 2025)
Along with the advancement of information and communication technology (ICT), the form of public participation has undergone a significant transformation from conventional to digital. This study aims to analyze the effectiveness of the implementation of digital-based public participation (e-Participation) in Indonesia, as well as to evaluate the regulatory and implementation challenges that hinder the realization of democratic, inclusive, and comprehensive public participation. The research method used is a normative juridical method (legal research) with a conceptual statute approach and a bibliography study. The results show that in its implementation, e-Participation in Indonesia still faces various obstacles, both from ambiguous regulations and from technical limitations and public participation. Based on factual data and findings, e-Participation has not been fully able to encourage broad and sustainable public involvement in the policy-making process. Therefore, reformulation and optimization of e-Participation are needed, both normatively through strengthening the legal framework, and technically through improving digital infrastructure, public literacy, and coordination between government agencies.